Canadian Law and Indigenous Self‐Determination A Naturalist Analysis - Christie, Gordon (University of Toronto Press, 2019)
For centuries, Canadian sovereignty has existed uneasily alongside forms of Indigenous legal and political authority. Canadian Law and Indigenous Self-Determination demonstrates how, over the last few decades, Canadian law has attempted to remove Indigenous sovereignty from the Canadian legal and social landscape. Adopting a naturalist analysis, Gordon Christie responds to questions about how to theorize this legal phenomenon, and how the study of law should accommodate the presence of diverse perspectives. Exploring the socially-constructed nature of Canadian law, Christie reveals how legal meaning, understood to be the outcome of a specific society, is being reworked to devalue the capacities of Indigenous societies. Addressing liberal positivism and critical postcolonial theory, Canadian Law and Indigenous Self-Determination considers the way in which Canadian jurists, working within a world circumscribed by liberal thought, have deployed the law in such a way as to attempt to remove Indigenous meaning-generating capacity